Financing Sustainable Development: Analysis of Modern Approaches and Practices in the Context of Financial and Credit Activities - Myronchuk, Viktoriia; Yatsenko, Oleksandr; Riznyk, Dmytro; Hurina, Olena; Frolov, Andrii (International Journal of Economics and Financial Issues, 2024)
This article explores sustainable development financing, using Monte Carlo simulation to reveal the project’s financial feasibility and possible hazards. To better assist project managers and investors, this study primarily seeks to provide quantitative insights into the profitability and risk profiles of sustainable development projects. Having this knowledge will allow them to make better decisions. In the Best-Case scenario, the average NPV was 250,000, with a standard deviation of 50,000. This demonstrates that, in a perfect world, there is a great deal of opportunity for profit. With a standard deviation of 20,000 and an average NPV of −50,000, the Worst-Case scenario presents a drastically different picture when confronted with bad conditions. This emphasizes the substantial financial dangers that are there. The Average Case scenario may be the most plausible given its 30,000 standard deviation and 110,000 average NPV. Specifically, the 15% chance of seeing negative NPV outcomes in this scenario emphasizes the inherent dangers. Through sensitivity analysis, we were able to identify operational expenses and revenue streams as the primary factors influencing these financial results. This further emphasizes their importance in determining the success or failure of the project. Sustainable investments can be made more attractive and viable with the help of regulatory frameworks that support them, financial incentives, and risk mitigation strategies like insurance, diversification, and government guarantees. There are already successful examples of the use of green bonds with state guarantees. This is despite the fact that funding sustainable development is full of financial uncertainties. In the end, the financial industry has to change, using new methods and tools to help the world move towards a more sustainable future, as the world community puts more emphasis on sustainability. This study highlights the need of using rigorous analysis and strategic planning to raise funds for sustainable development including green bond and green investors, providing a framework for achieving a balance between financial success and social and environmental responsibility.